Gender Diversity in Audit Committees and Its Impact on Financial Reporting Quality: A Narrative Review - Kartika, Erawati; Ungkari, Marti Dewi; Syakinah, Fitri (Indonesian Scientific Publication, 2025)
The relationship between gender diversity in audit committees and financial reporting quality has become an important theme in corporate governance research. This review consolidates empirical and theoretical evidence on how female representation affects audit quality, earnings management, fraud prevention, tax behavior, and sustainability disclosures. Using a systematic search across Scopus, Web of Science, and Google Scholar, we included peer-reviewed studies published in the last decade. The findings show that gender-diverse audit committees strengthen oversight, reduce misreporting, discourage aggressive tax strategies, and enhance ESG disclosure. Comparative evidence indicates stronger effects in developed economies with regulatory mandates, while cultural and institutional barriers in developing markets often limit effectiveness. Unlike previous reviews, this study highlights the combined influence of gender diversity on financial integrity and sustainability reporting, offering an integrated governance perspective. Policy implications include the adoption of gender quotas, leadership training for women, and mandatory disclosure of board diversity. Future research should explore longitudinal trends, sectoral variations, and mechanisms linking gender diversity with governance outcomes.